Full On-chip low dropout voltage regulator with an enhanced transient response for low power systems - Hatim Ameziane; Kamal Zared; Hicham Akhamal; Hassan Qjidaa (Institute of Advanced Engineering and Science, 2019)
A full on chip low Dropout Voltage Regulator (LDO) with fast transient response and small capacitor compensation circuit is proposed. The novel technique is implemented to detect the variation voltage at the output of LDO and enable the proposed fast detector amplifier (FDA) to improve load transient response of 50mA load step. The large external capacitor used in Conventional LDO Regulators is removed allowing for greater power system integration for system-on-chip (SoC) applications. The 1.6-V Full On-Chip LDO voltage regulator with a power supply of 1.8 V was designed and simulated in the 0.18µm CMOS technology, consuming only 14 µA of ground current with a fast settling-time LNR(Line Regulation) and LOR(Load regulation) of 928ns and 883ns respectively while the rise and fall times in LNR and LOR is 500ns.